4-Hydroxypyridinium-3-sulfonate - Zhu, Zhi Biao; Gao, Shan; Ng, Seik Weng (International Union of Crystallography, 2011)
The reaction of 4-hydroxypyridine and oleum produces 4-hydroxypyridinium-3- sulfonate, C5H5NO4S, which shows delocalized bonds in the six-membered ring. In the crystal, adjacent zwitterions are linked by N - H⋯O and O - H⋯O hydrogen bonds into a layer motif. The crystal studied was a racemic twin.